Pengembangan Chatbot untuk Meningkatkan Pengetahuan dan Kesadaran Keamanan Siber Menggunakan Long Short-Term Memory - Hilya Anbiyani Fitri Muhyidin; Liptia Venica (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2023)
Cyber-crime is becoming more massive as online activities increase. Cybercrime is a criminal act that exploits digital technology to damage, harm, and destroy property. Therefore, it is crucial for internet users to have knowledge of cybersecurity and the world of technology and the internet in order to avoid falling victim to cybercrime. The aim of this study is to develop a chatbot system as a centralized information medium on cybersecurity, technology, and the internet for internet users. The development of this chatbot aims to reduce the risks of cybercrimes and help enhance internet users' awareness of cybercrime. This research employs the AI Project Cycle method in chatbot development and utilizes the Long Short-Term Memory (LSTM) deep learning model algorithm to develop a model that achieves high accuracy. The training results of the LSTM model achieved an accuracy score of 100% and a loss of 3.09% with 400 epochs. Consequently, it can be concluded that the LSTM algorithm is highly effective for training and developing a chatbot model.